IMPLEMENTATION OF HOTS BASED PROJECT BASED LEARNING (PjBL) TO CREATE INNOVATIVE LEARNING MEDIA - Jelita Panjaitan; Ika Trisni Simangunsong; Humiras Betty M. Sihombing (Universitas Negeri Medan, 2020)
This study aims at determining how HOTS-based Project Based Learning (PjBL) plays a role in increasing student innovation to create learning media. This research uses a qualitative descriptive approach that was carried out in the Physics Education Study Program, Teacher Training and Education Faculty, Darma Agung University. This research is a quasi-experimental study with a two group Pre-test and Post-test design. The research population is all sixth semester students of the Physics Education Study Program, Teaching and Education Faculty, Darma Agung University, Medan. The sample in this study was taken by total sampling, as many as 2 classes totaling 30 people. Morning class is determined as an experimental class that is taught by HOTS-based PjBL model that consists of 15 students, Afternoon class as control class is taught using direct instruction model consisting of 15 students. The research instrument uses HOTS essay test consisting of 10 questions and innovation to create learning media in the form of a questionnaire consisting of 10 cases and has been declared valid and reliable. The resulting data were analyzed using two-way ANOVA. The results show that HOTS-based PjBL is better applied than the direct instruction model because this learning method can increase students' innovation to create better learning media. This can be seen in the link https://www.youtube.com/watch?v=MWY6Rv7BL8o&feature=youtu.be.